Management of peritoneal surface metastases from colorectal cancer: Cytoreductive surgery, hyperthermic intraperitoneal chemotherapy, pressurized intraperitoneal chemotherapy, and beyond - Mangieri, Christopher W.; Levine, Edward A. (Frontiers in Oncology, 2022)
This article provides a contemporary review of the current surgical management of peritoneal surface malignancy (PSM) of colorectal origin. A brief review of the founding history of surgical intervention for PSM is followed by a focused review of the level I evidence, current clinical questions, and evolving advancements. While not intended to address all the facets of PSM, this review aims to provide the reader with the essential knowledge and resources to effectively provide surgical care for carcinomatosis due to colorectal malignancies.